LEGAL IMPACT OF BUSINESS DISPUTES IN MARRIAGE ON OWNERSHIP AND DIVISION OF JOINT PROPERTY - Beby Sendy; Rika Jamin Marbun; Tria Wahyu Artita (International Journal of Society and Law, 2025)
Marriage is a sacred institution that is not only physically binding, but also affects the legal, social, and moral aspects of human life. One of the important issues in marriage is the division of joint property, especially during a divorce. Joint property refers to all property acquired by a husband and wife during the marriage. However, there are various factors that influence the division of joint property, including the type of property owned, the marriage agreement made previously, and the contribution of each party to the business or property acquired. The division of joint property is regulated by Law Number 1 of 1974 concerning Marriage and the Civil Code, which provide a legal basis for the assessment and resolution of disputes related to joint property. This study aims to examine the definition and scope of joint property in marriage and the mechanism for resolving business disputes that arise due to divorce. The method used is normative juridical with a descriptive analytical approach, through an analysis of relevant laws and regulations and jurisprudence. The results of the study indicate that the division of joint property in the context of divorce involves a process of mediation, litigation, and evaluation of the contribution of each party in obtaining the property. In addition, there are exceptions to joint property, such as personal property or property acquired through a prenuptial agreement.